"I try and be as athletic like, forget the other side of me" - Constructions of Elite Female Wheelchair Athletes' Identities - Wickman, Kim (Kvinder, Køn & Forskning, 2004)
For an athlete to participate in the Olympics is a sign of supreme achievement. The same could as well be the case for those who participate in the Paralympics, the equivalent of the Olympics. The way elite female wheelchair athletes talk about themselves and their sport and their ecperience of being positioned by others and the way position themselves will be discussed in this paper.